Morphological findings in bone marrow biopsy and aspirate smears of visceral kala azar: A review - Dhingra Kajal; Gupta Parul; Saroha Vijay; Setia Namrata; Khurana Nita; Singh Tejinder (Wolters Kluwer Medknow Publications, 2010)
Context: Visceral leishmaniasis (VL) is endemic in India and may simulate and cause many hematological disorders like pancytopenia, myelofibrosis, myelodysplasia and hemophagocytosis. Aims: The study aims to investigate the hematological manifestation of Visceral Leishmaniasis and associated changes that may be observed in bone marrow aspirate smears and biopsy which may warn a pathologist of possible infections. Settings and Design: This is a retrospective study of 18 VL cases on B (b) one marrow aspirate and biopsy in the department of Pathology in a tertiary care teaching hospital in New Delhi. Methods and Material: Giemsa stained slides of bone marrow aspirates and hematoxylin and Eosin stained biopsy slides were reviewed in detail by two competent pathologists. All the findings were tabulated and discussed and comparisons made with the previous similar studies. Results: Hyper cellular marrow, increased lymphocytes and plasma cells, marrow granulomas, hemophagocytosis, myelofibrosis, myelodysplasia and gelatinous transformation of the marrow were notable features the presence of which together or individually should caution a pathologist to search for Leishman Donovan (LD) bodies in patients especially in a non-endemic zone in a tropical country.